Adaptation of a parasitic lifestyle by Cuscuta gronovii Willd. ex Roem. & Schult.: large scale gene deletion, conserved gene orders, and low intraspecific divergence. Issue 4 (3rd April 2021) - Ni, Yang; Jiang, Mei; Chen, Haimei; Huang, Linfang; Chen, Pinghua; Liu, Chang
Abstract: Cuscuta gronovii Willd. ex Roem. & Schult. is a parasitic plant and widely distributed in Europe and North America. Here, we compared the plastome sequences of a C. gronovii plant collected from China and other 16 Cuscuta plastomes, including one C. gronovii plastome from North America. The plastome was 86, 727 bp in size with a pair of inverted repeats (IRs) of 14, 354 bp, a large single-copy (LSC) region of 50, 956 bp, and a small single-copy (SSC) region of 7, 063 bp. We predicted 97 genes in the plastome, including 61 protein-coding genes, eight ribosomal RNA genes, and 28 transfer RNA genes. We detected a total of 21 microsatellite, 16 tandem, and ten interspersed repeats in the genome. Gene contents analysis of 17 Cuscuta plastomes showed the loss of the entire ndh gene family. The phylogenomic analysis using 22 shared protein sequences shows that the two C. gronovii formed a cluster. Thirteen of Cuscuta plastomes showed no rearrangement. The other three showed smaller inversions and smaller numbers of gene deletion. Next, we identified the two INDELs, one SNP site between the two C. gronovii plastomes. And we identified two putative RNA editing sites. Lastly, to distinguish between C. gronovii and two medicinal Cuscuta species, C. chinensis and C. australis, we identified ten molecular markers based on the genome sequences. The overall large-scale gene loss, conserved gene order, low intraspecific divergence are consistent with the adaptation of C. gronovii to a parasitic lifestyle.